DNA methylation-predicted plasma protein levels and breast cancer risk - Jacob K. Kresovich; Brett M. Reid; Katie M. O’Brien; Zongli Xu; Doratha A. Byrd; Clarice R. Weinberg; Dale P. Sandler; Jack A. Taylor (Breast Cancer Research)
Abstract Background Blood DNA methylation (DNAm) profiles have been used to show that changes in circulating leukocyte composition occur during breast cancer development, suggesting that peripheral immune system alterations are markers of breast cancer risk. Blood DNAm profiles have recently been used to predict plasma protein concentrations (“Protein EpiScores”), but their associations with breast cancer risk have not been examined in detail. Methods Whole blood DNAm profiles were obtained for a case-cohort sample of participants in the Sister Study and used to calculate 109 Protein EpiScores. Of the 4,479 women included, 2,151 (48%) were diagnosed with breast cancer within 15 years of their baseline blood draw (median time to diagnosis: 8.6 years; 1,673 invasive cancer and 478 ductal carcinomas in situ). Protein EpiScores associations with breast cancer incidence were estimated using weighted Cox regression models, overall and stratified by time and participant characteristics. Results Protein EpiScores for RARRES2, IGFBP4, and CCL21 were positively associated with invasive breast cancer risk (hazard ratios from 1.17 to 1.24), while those for F7, SELL, CXCL9, CD48, and IL19 were inversely associated (hazard ratios from 0.82 to 0.86) (all FDR < 0.10). Eight immune response-related Protein EpiScores (CXCL9, CD48, FCGR3B, CXCL11, CCL21, CRTAM, VCAM1, GZMA) were associated with invasive cancers diagnosed within five years of enrollment. Protein EpiScore associations were consistently stronger for estrogen receptor-negative tumors. Conclusions Several Protein EpiScores, including many related to immune response, were associated with breast cancer risk, highlighting novel changes to the peripheral immune system that occur during breast cancer development.